Cambio conceptual y metodológico en la enseñanza y el aprendizaje de la evolución de los seres vivos. Un ejemplo concreto - Gené, A. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
In this work we developed and assessed the efficiency of a didactic lesson based on the science teaching learning paradigm as a conceptual, methodological and attitudinal change. For this purpose we chose the topic of the evolution of living beings through natural selection.